The influence of eco-labelling on consumer behaviour - results of a discrete choice analysis for washing machines - Sammer, Katharina; Wüstenhagen, Rolf (Business strategy and the environment, 2006)
Eco‐labelling is an important tool to overcome market failure due to information asymmetries for environmental products. While previous research has discussed the importance of labelling, this paper provides empirical data on the influence of eco‐labels on consumer behaviour for household appliances. It reports on the results of a survey involving a total of 151 choice‐based conjoint interviews conducted in Switzerland in Spring 2004. Choice‐based conjoint analysis (also known as discrete choice) has been applied to reveal the relative importance of various product attributes for consumers. The EU energy label is used for the product category chosen in our survey, washing machines, and we investigate the relative importance of this eco‐label compared with other product features (such as brand name) in consumers' purchasing decisions. We draw conclusions for sustainability marketing and policy. Copyright © 2006 John Wiley & Sons, Ltd and ERP Environment.